PENERAPAN METODE TANYA JAWAB UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS VI SD NEGERI 012 PANGKALAN BARU KECAMATAN SIAK HULU - Samsul Ependi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The fundamental problem that is always faced in learning Indonesian in SD Negeri 012 Pangkalan Baru is the low activity andlearning achievement of students whose development is less encouraging. Therefore this research was conducted aimed atovercoming these problems by applying the question and answer method. This research is a classroom action researchconducted in class VI of SD Negeri 012 Pangkalan Baru. The results showed that the activity and learning outcomes increased,in cycle 1 meeting 1 student activity score was 15.38%, at meeting 2 was 22.11%, at meeting 3 it reached a score of 28.85%. Incycle 2 meeting 2 student activity scores were 36.59%, at meeting 2 was 41.34%, and at meeting 3 was 77.88%. Based on theseresults it can be concluded that the question and answer method can improve the learning achievement of Indonesian.